Green Economy Initiatives in Enhancing Social Solidarity in the Tourism Sector in Coastal Areas - Muhammad Syahrul Hidayat; Asramid Yasin; Rahayu Sulistiowati; Desideria Regina; Trinandari Prasetyo Nugrahanti (GoAcademica Research & Publishing, 2023)
The tourism sector is an essential part of the coastal area. Therefore, there is a need for sustainable maintenance so that the tourism sector is maintained. The development of a sustainable tourism sector can be implemented through the green economy. In practice, the implementation of this green economy can also be used to increase solidarity among communities. This research then aims to see how green economy initiatives can increase social solidarity in the tourism sector in coastal areas. This research will be carried out using a descriptive qualitative approach. The data used in this study come from different research results and previous studies, which still have relevance to the contents of this research. The study results then found that the tourism sector in coastal areas has various challenges and obstacles. However, this problem can be solved by implementing a green economy. Through environmentally friendly practices, this can provide economic and social benefits that are more equitable to local communities. Then community involvement can be increased in managing the tourism sector, thereby strengthening environmental awareness and local culture. This, in turn, can increase social solidarity in society.